The Importance of Game-Based Learning in English Learning for Young Learners in the 21st Century - Ningsih, Ni Luh Ayu Budi Hari (The Art of Teaching English as a Foreign Language (TATEFL), 2023)
The game is an activity that is very popular with everyone, especially for young learners. Currently, many teachers have applied games into learning activities, and this method is called game-based learning. Game-based learning has many benefits and has an effect on teaching and learning activities. This study aimed to systematically review studies on game-based learning for elementary children in the 21st century learning in Indonesia. Literature analysis was carried out with a total of 7 journals analyzed in a systematic review. Based on research results, game-based learning has advantages in the teaching and learning process of English by making learning interesting, making it easier for young students to understand material such as vocabulary mastery and affecting students’ capacity to create imaginative abilities, basic considering and digital skills. In addition, game-based learning shows positive perceptions in learning by being able to increase students' motivation in learning English.